PROGRAM PENGEMBANGAN KEWIRAUSAHAAN KERUPUK KULIT SINGKONG - Santosa, Alam; Robecca, Julian (Indonesian Community Service and Empowerment Journal (IComSE), 2024)
The Cassava Peel Cracker Entrepreneurship Development Program is a training program for students who have started entrepreneurship. The training covers aspects of marketing, production, finance, and legal. The result of the training is the identification of aspects that need to be improved to increase product competitiveness in the market. And produce outputs in the form of product prototypes, online stores and intellectual property rights.